Stories of Design Education: An Analysis of Practices and Competencies. (May 2022) - Thandlam Sudhindra, S.; He, Y.; Blessing, L.; Ahmad Khan, S.
Abstract: Using 61 stories from design educators from different countries, this paper presents (1) the design competencies being fostered at different levels of education, (2) the practices (approaches, techniques, methods and tools) used to facilitate teaching and learning, (3) the 'non-design' competencies being fostered, and (4) the impact of COVID 19. Our findings highlight design education is not only used to teach students how to design, but also to kindle productive attitudes, behaviours and mindsets that give them the ability to address a wide range of challenges.